UMP Excels in The Research Area of PV Module Cooling - Sudhakar, K. (Faculty of Mechanical & Automotive Engineering Technology, 2022)
UMP research team led by Dr. Sudhakar Kumarasamy in collaboration with Russian and Indian researchers have been working on cooling solutions for photovoltaic modules over the past few years.